Evaluation of shared-view acquisition using repeated echoes (SHARE): a dual-echo fast spin-echo MR technique. - Johnson, B A; Fram, E K; Drayer, B P; Dean, B L; Keller, P J; Jacobowitz, R (American Journal of Neuroradiology, 1994)
PURPOSE To compare the clinical efficacy of a dual-echo fast spin-echo imaging technique, SHARE (share-view acquisition using repeated echoes), with conventional long-repetition-time spin-echo imaging. METHODS Conventional spin-echo and SHARE fast spin-echo MR images of the brain were acquired in 50 randomized patients and interpreted separately in conjunction with the T1-weighted images. All images were reviewed independently by two neuroradiologists who were blinded to the clinical history and previous interpretations. RESULTS The diagnoses rendered for the spin-echo and SHARE images were concordant in 48 of the 50 subjects (96%) by the first reader and in all 50 cases (100%) by the second reader. SHARE images were acquired in one-fourth of the imaging time yet image contrast, quality, and sensitivity to long T2 lesions were comparable. The SHARE technique was less sensitive to hemorrhagic residua. CONCLUSIONS SHARE is a viable time-saving alternative to the conventional long-repetition-time pulse sequence. Although SHARE images are not as sensitive to magnetic susceptibility effects, the time saved using this technique could be used to perform a gradient-echo sequence when indicated.